Pengaruh Pertumbuhan Kredit, Pertumbuhan Laba, Non Performing Loan (NPL) Terhadap Harga Saham Perusahaan Perbankan Yang Terdaftar Di Bursa Efek Indonesia - Alwi Alwi; Muhammad sayid Fadil (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
This research aims to determine the influence of credit growth, profit growth and non-performing loans (NPL) on share prices of banking sector companies listed on the Indonesia Stock Exchange 2018-2022. Data analysis tests used Multiple Linear Regression Analysis, Classical Assumption Tests (Normality, Multicollinearity, Heteroscedasticity, Autocorrelation), Test, Coefficient of Determination R2, Simultaneous F Test, and Partial t Test. The population in the research are banking companies that have gone public and have been registered and listed on the Indonesian Stock Exchange. Meanwhile, the sample for this research is banks registered in the Banking Group of Bank Groups Based on Core Capital (KBMI IV) in 2018-2022, totaling 4 Banking Entities. The research results show that Credit Growth, Profit Growth and Non-Performing Loans (NPL) each partially have a significant positive effect on Stock Prices. The results of this research simultaneously credit growth, profit growth and non-performing loans (NPL) together have a significant positive effect on KBMI IV Banking share prices 2018-2022.